IMAGING OF SEVERE RENAL AND LIVER INJURY ON A TRAUMA PATIENT: A CASE REPORT - Pamarta, Trisna Belani; Nabila, Astrid Hanan; Karliasari, Liana (Department of Radiology, Medical Faculty, University of Brawijaya, 2024)
Blunt abdominal trauma accounts for the most abdominal injuries. A quick yet accurate examination must be carried out immediately to identify and promptly address the cause of the internal bleeding. In this case report, we describe A 17-year-old girl who was taken to the emergency room after she lost consciousness following a traffic accident. The patient presented with unstable hemodynamics indicating signs of hemorrhagic shock. The patient then underwent a CT examination with contrast to determine the diagnosis. The patient was diagnosed with internal bleeding with unstable hemodynamics due to liver injury AAST grade IV and renal trauma AAST grade III. In this case, signs of kidney and liver trauma can be recognized, such as fluid accumulation and the severity of injury to each organ. This case report aims to increase awareness of the signs of intra-abdominal bleeding and its severity so that appropriate treatment can be determined immediately. Keywords: renal injury, liver injury, abdominal CT-Scan